Physicochemical Characterization of a Cellulosic Film Modified with Two Room-Temperature Ionic Liquids - Martinez de Yuso, Maria del Valle; Cuevas, Ana Laura; Benavente-Herrera, Juana (IOAP-MPDI, 2022)
Changes in the physicochemical characteristics of a regenerated cellulose (RC) film due to a surface modification with room-temperature ionic liquids (ILs) are determined. Two ILs (1-butyl-3-metylimidazolium hexafluorophosphate and tricaprylmethylammonium chloride) were selected, and film surface modification was performed by a dip-coating process (1 h) in the corresponding IL. The surface characterization of the RC/IL films was carried out by XPS at various take-off angles (from 15° to 75°), while the modification of mechanical properties was established by tensile analysis, obtaining a significant increase for the Young modulus of both RC/IL films when compared with the RC-support. Optical characteristics of the RC/IL films were determined by transmittance and reflectance measurements for wavelengths covering visible and near-infrared regions, while impedance spectroscopy (IS) measurements allow us to estimate the electrical changes in the RC/IL films. These results show the high transmittance of both RC/IL films (>90%) with slight differences depending on the IL in both optical regions, while the IS data analysis indicated a conductivity reduction and dielectric constant increase in the dielectric constant for both eco-friendly RC/IL films
Keywords: Optica electrónica; Film modification; Lonic liquids; XPS; Mechanical effect; Optical; Eectrical changes